Adequacy of Community Social Work in favor of Partcipation in Chile: La Contraloría Social mecanismo desde lo Municipal para la Cohesión Social - Sanhueza Cisterna, Adriana (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The present investigation is a qualitative investigation of a descriptive type, developed for the doctorate in Social Work, of the Rovira I Virgili University, one of its objectives is to carry out a rescue and adaptation of the socio-community social work to strengthen post-crisis participation of liberal democracy or particularly Chilean neoliberal democracy. Therefore, some considerations and advances linked to the methodology and the information collection procedure are presented, as well as the first results of the applied research work